EVALUASI IMPLEMENTASI PELAYANAN INFORMASI OBAT PASIEN RAWAT JALAN DI INSTALASI FARMASI RUMAH SAKIT YOGYAKARTA - Farida Baroroh (Pharmaciana, 2011)
To support high quality health service in hospital, Pharmacy Installation ofYogyakarta Hospital needs to evaluate implementation of drug information service foroutpatient. This study is aimed to identify the realization of drug information service ofoutpatient implementation of Pharmacy Installation of Yogyakarta Hospital comparedto the specified target. This study was carried out by descriptive design using secondarydata of Pharmacy Installation programs, interview with a pharmacist was assignedoutpatients serving as research subjects, as well as direct observation of druginformation service for outpatient. Gap analysis was used to identify the comparisonbetween the realization and specified target. The result of this study of evaluation indrug information service implementation of outpatient showed negative gaps as muchas -0.67%. The component information presented included the efficacy of drugs, how touse, the rules of use, duration of drug use, drug side effects, however the components ofdrug information that is unallowed in Pharmacy Installation of Yogyakarta Hospitalhow shcedule of drug use and signs toxicity.